2007
DOI: 10.1007/s10460-006-9034-0
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Southeast Asia to the Southeast United States: New forms of alternative agriculture in Homestead, Florida

Abstract: Immigrant farmers from Southeast Asia have brought knowledge of tropical fruit and vegetable production from their home countries to Homestead, Florida. They have developed a new style of farming, one that most closely resembles agricultural systems described as ''homegardens.'' Although biodiverse agricultural systems are generally thought to be commercially unviable, homegarden farmers successfully manage crop diversity as an economic strategy. By focusing on growing a mixture of specialty Southeast Asian he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…These goals, values, and motivations are influenced by the demographic characteristics of the farm family (Colman & Elbert, 1984;Gasson, 1973;Gasson & Errington, 1993;Lobley & Potter, 2004;Salamon, 1992;Shucksmith & Herrmann, 2002). The associations among gender, ethnicity, culture, length of time farming, farm structure, and development have been well documented in the literature (Imbruce, 2007;Sachs, 1996;Salamon, 1992;Wells & Gradwell, 2001.…”
Section: Farmer Diversity At the Ruimentioning
confidence: 99%
See 1 more Smart Citation
“…These goals, values, and motivations are influenced by the demographic characteristics of the farm family (Colman & Elbert, 1984;Gasson, 1973;Gasson & Errington, 1993;Lobley & Potter, 2004;Salamon, 1992;Shucksmith & Herrmann, 2002). The associations among gender, ethnicity, culture, length of time farming, farm structure, and development have been well documented in the literature (Imbruce, 2007;Sachs, 1996;Salamon, 1992;Wells & Gradwell, 2001.…”
Section: Farmer Diversity At the Ruimentioning
confidence: 99%
“…Wells (1996) also has shown the linkage between ethnicity and farming subsystems in California strawberry production, finding that Japanese, Mexican and Anglo growers brought different sets of resources to their farms' development, and that the different social networks associated with each ethnic group created and reinforced farm management styles over time. Recent research on immigrant farmers from Southeast Asia in the Miami Metro region found that the unique motivations, social networks, and style of farming (intensive and diverse) has enabled these small family farms to thrive by taking advantage of niche markets and national distribution networks despite high land rents (Imbruce, 2007). The increase in the number of Hispanic, Asian, Native American and African American farmers (USDA, NASS, 2007a) reinforces the need to understand how cultural nuances influence larger production patterns on the RUI landscape.…”
Section: Ethnicity and Racementioning
confidence: 99%
“…Therefore, the absence of immigrants might have supported plant diversity of the homegardens. However, immigrants were found to introduce new skills in managing homegardens and making them more fruitful (Imbruce, 2007). Therefore, the absence of immigration may have affected the development of homegarden land use which is reflected in the number of homegardens in the village.…”
Section: Discussionmentioning
confidence: 99%
“…Tree density was reported to be 342 ± 74 trees ha Tree class (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was the most abundant with a share of 74% of total tree density. There was a sharp decline in tree density from lower to higher diameter classes with class 40-50 cm DBH as an exception, since no trees were reported in this class.…”
Section: Study Areamentioning
confidence: 99%
“…However, as summarised in Chapter 1, alternative food networks continue to be framed as a relatively recent phenomenon associated with alternative agri-food movements and/or niche markets for elite consumers and consumers concerned with food safety. The alternative food networks literature largely ignores the work of farmers of colour and the food networks in which they are involved (but see Alkon & Norgaard, 2009;Alkon, 2007;Imbruce, 2007).…”
Section: Are Chinese-canadian Farmers Involved In Alternative Food Nementioning
confidence: 99%